2023
DOI: 10.1186/s13023-023-02639-z
|View full text |Cite
|
Sign up to set email alerts
|

Areas of improvement in the medical care of SMA: evidence from a nationwide patient registry in Germany

Abstract: Background Management and treatment of spinal muscular atrophy (SMA) has changed in recent years due to the introduction of novel transformative and potentially curative therapies resulting in the emergence of new disease phenotypes. Yet, little is known about the uptake and impact of these therapies in real-world clinical practice. The objective of this study was to describe current motor function, need of assistive devices, and therapeutic and supportive interventions provided by the healthca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…However, an additional explanation for this "lower respiratory prevalence" could be due to the gradual progression of symptoms, with patients adapting their daily activities and not actively reporting respiratory problems. It may also be due to increased "medical awareness" within the healthcare community, which is now more vigilant than in previous years in monitoring and treating any co-morbidities associated with SMA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an additional explanation for this "lower respiratory prevalence" could be due to the gradual progression of symptoms, with patients adapting their daily activities and not actively reporting respiratory problems. It may also be due to increased "medical awareness" within the healthcare community, which is now more vigilant than in previous years in monitoring and treating any co-morbidities associated with SMA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The classification of SMA is evolving from traditional subtypes to a more detailed approach that considers the age of onset, number of SMN2 copies, age at initiation of drug treatment, and current motor function levels (non-sitter, sitter, walker) to define clinical phenotypes. This allows for more precise monitoring of disease progression and enhances the tailoring of medical care [ 32 , 56 ].…”
Section: New Therapiesmentioning
confidence: 99%
“…These drugs have been shown to have the potential to transform the natural disease evolution, thereby challenging the traditional classification of patients into static subtypes [5][6][7]. Indeed, we have shown that improvements to the medical management, including the introduction of novel therapies, appears to have altered the disease trajectory among children and adults with SMA in Germany [8]. As a result, in line with current standards of care, a complementary disease classification, made in terms of current best motor function of the lower limb and trunk, has been proposed for SMA in response to the observed changes in patterns of morbidity and disability [9,10].…”
Section: Introductionmentioning
confidence: 96%